Bacterial communities associated with honeybee food stores are correlated with land use. Issue 10 (16th April 2018) - Donkersley, Philip; Rhodes, Glenn; Pickup, Roger W.; Jones, Kevin C.; Wilson, Kenneth
Abstract: Microbial communities, associated with almost all metazoans, can be inherited from the environment. Although the honeybee ( Apis mellifera L.) gut microbiome is well documented, studies of the gut focus on just a small component of the bee microbiome. Other key areas such as the comb, propolis, honey, and stored pollen (bee bread) are poorly understood. Furthermore, little is known about the relationship between the pollinator microbiome and its environment. Here we present a study of the bee bread microbiome and its relationship with land use. We estimated bacterial community composition using both Illumina MiSeq DNA sequencing and denaturing gradient gel electrophoresis (DGGE). Illumina was used to gain a deeper understanding of precise species diversity across samples. DGGE was used on a larger number of samples where the costs of MiSeq had become prohibitive and therefore allowed us to study a greater number of bee breads across broader geographical axes. The former demonstrates bee bread comprises, on average, 13 distinct bacterial phyla; Bacteroidetes, Firmicutes, Alpha‐proteobacteria, Beta‐proteobacteria, and Gamma‐proteobacteria were the five most abundant. The most common genera were Pseudomonas, Arsenophonus, Lactobacillus, Erwinia, and Acinetobacter . DGGE data show bacterial community composition and diversity varied spatially and temporally both within and between hives. Land use data were obtained from the 2007 Countryside Survey. Certain habitats, such as improved grasslands, are associated with low diversity bee breads, meaning that these environments may be poor sources of bee‐associated bacteria. Decreased bee bread bacterial diversity may result in reduced function within hives. Although the dispersal of microbes is ubiquitous, this study has demonstrated landscape‐level effects on microbial community composition. Abstract : As these microbial communities are generally inherited from their host's environment, we examined how the landscape composition surround beehives contributes to microbial community. We report strong correlations between the bacterial community of bee bread and the land use composition. Specifically, that communities were more diverse with increasing natural grasslands cover, and less diverse in areas surrounded with agricultural improved landscape types.